2018
DOI: 10.1088/1367-2630/aa9ca2
|View full text |Cite
|
Sign up to set email alerts
|

Spin-gap spectroscopy in a bosonic flux ladder

Abstract: Ultracold bosonic atoms trapped in a two-leg ladder pierced by a magnetic field provide a minimal and quasi-one-dimensional instance to study the interplay between orbital magnetism and interactions. Using time-dependent matrix-product-state simulations, we investigate the properties of the so-called 'Meissner' and 'vortex' phases which appear in such a system, focusing on the experimentally accessible observables. We discuss how to experimentally monitor the phase transition, and show that the response to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Several interesting properties have been highlighted by a number of works, for both bosonic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and fermionic [53][54][55][56][57][58][59][60][61] flux ladders. Importantly, it was shown that flux ladders, in the quasi-1D limit, can host states that share fundamental properties with 2D FQH states [62][63][64][65], and that can be directly tested in current cold-atom experiments as well as DMRG or MPS simulations [64,65].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Several interesting properties have been highlighted by a number of works, for both bosonic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and fermionic [53][54][55][56][57][58][59][60][61] flux ladders. Importantly, it was shown that flux ladders, in the quasi-1D limit, can host states that share fundamental properties with 2D FQH states [62][63][64][65], and that can be directly tested in current cold-atom experiments as well as DMRG or MPS simulations [64,65].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In the context of the ladder model, Eq. ( 1), other distribution functions that are related to n(k) have been considered [26,53,54], as follows.…”
Section: Leg-resolved Mdfsmentioning
confidence: 99%
“…Moreover, the possible existence of Laughlin-like states has attracted great interest [44][45][46][47][48][49] and the study of the Hall effect in flux ladders remains an active line of research [50][51][52][53]. At the same time, proposing adequate methods to probe these phases, i.e., via spectroscopic [54][55][56], transport [57][58][59][60], or microscopic probes, or via global measurements, remains an important question.…”
Section: Introductionmentioning
confidence: 99%